(untitled) (Research, Society and Development, 2022)
Introduction: In judo competitor athlete preparation includes sessions with specific technical training, strength training with resistance exercise, power and endurance training. The high demand for training and the limited time for recovery can pose a risk for the onset of injury and trigger the overtraining state. Objective: To identify in the literature the methods and procedures adopted for the identification of training intensity and indicators of overtraining in judo athletes. Methodology: We searched the Pubmed, Lilacs, Scielo and Scopus databases. The terms "judo", "overtraining" and "training intensity monitoring" were used as descriptors. To evaluate the quality of the articles, the Delphi table was used. Results: All the studies used metabolic and biochemical analysis to identify the markers of overtraining and training intensity. Three studies also used PSE as an instrument to identify training loads. Conclusion: The identification of the excessive intensity of the training as well as the detection of overtraining situation in judo athletes has been performed by means of biochemical and metabolic analysis.